Document classification based on kNN algorithm by term vector space reduction - Moldagulova A.; Sulaiman R.B. (IEEE Computer Society, 2023)
Classification (of information); Data handling; Data mining; Information retrieval systems; Learning algorithms; Text processing; Vectors; Document Classification; Space reductions; Text classifiers; Text mining; Textual data; Unstructured data; Vector spaces